PENILAIAN KEPEMIMPINAN KEPALA SEKOLAH BERBASIS AGAMA, FILOSOFIS, PSIKOLOGI DAN SOSIOLOGI Studi Kasus di Dinas Pendidikan Provinsi DKI Jakarta - Marpudin, Ade; Handoko, Gatot; Abdulhak, Ishak; Mudrikah, Ahmad (ISLAMIKA, 2021)
Assessment in leadership is an important part of the management function, namely controlling (supervision/assessment) to measure the progress and performance of the Principal. And the Principal's Leadership Assessment cannot be separated from the foundations of religion, philosophy, psychology and sociology. The results will have an influence on efforts to improve leadership in an education towards change, improvement, improvement, development and maintaining the achievements that have been achieved in the institution, so that it is a quality and superior educational institution. The study method and approach used in the research is through an approach approach, namely by conducting a literature review and field study. Data was collected through Interview, Observation and Documentation. The data were analyzed through the process of data reduction, data presentation and drawing conclusions. Management problems in school governance are problems that are often not in accordance with the complexity of environmental changes, both in terms of planning, coordination, implementation, direction and supervision (evaluation). The development of school principals carried out by the government (through the education office) has not yet given maximum results in improving the quality of education. This happens because the empowerment of all components in the school environment has not been optimal. However, the implementation of the assessment on the basis of religion, philosophy, psychology and socialism on the leadership of the Head of the DKI Jakarta Education Office is clearly visible in the supervision process, this can be seen in clearly written points (indicators), for example having noble character, being an example of noble character, honest attitude, commitment and integrity.